(untitled) (Arquivos do Mudi, 2023)
Dietary restriction during pregnancy and puberty is a risk factor to hypertension onset at adulthood. The aim of this study was to evaluate the effect of maternal malnutrition during lactation on cardiovascular parameters, in both sexes of rat pups at 120-day-old. Maternal food restriction lead to arterial hypertension, baroreflex impairment, cardiac remodeling and increased collagen deposition in the aorta, in adult male offspring. The females did not show functional or morphological disruptions. Together, these results show that maternal food restriction during lactation promotes cardiometabolic programming, generating cardiovascular alterations in male adult rat offspring, however female offspring present some kind of cardioprotective effect.